Can Electronic Land Rights Registration Help Prevent Land from Mafia Practices? - Rosmidah, Rosmidah; Supeno, Supeno; Fathni, Indriya; Abubakar, Yusuf Sani (Faculty of Law, Jambi University, 2024)
The high demand for land causes the state to regulate the land ownership and registration system to create an orderly land administration. Unfortunately, according to the Ministry of ATR/BPN in 2024, 45 percent of land has not been registered administratively, either through systematic or sporadic registration. This situation creates an opportunity for irresponsible individuals to control land through the use of land mafia networks illegally. This study aims to find the legal certainty of electronic land registration. The problem is whether or not electronic land registration can prevent land mafia practices. Through normative legal research, it is concluded that one such model that works well to ensure the prevention of land mafia is the implementation of an electronic land registration system. This approach is aligned with the use of technology in the digital era, offering more practicality and modernity, while also providing enhanced legal certainty over land ownership. Thus, electronic land registration is essential for the anti-land mafia